Urban solid residues: An analises of logistical process and the operation of cooperativas at Belém (Research, Society and Development, 2020)
The inadequate accumulation of solid urban waste threatens daily living conditions in cities, with high social and environmental costs, in addition to impacts on the landscape. In this sense, waste pickers' cooperatives have a fundamental role in promote the return of different materials to the production cycle, preventing them from being destined to landfills. Thus, it should be noted that a problem is generated due to this necessary class of better working and living conditions since they act on the tripod of sustainability management, therefore, this article aimed to understand the processes of collecting, transporting and marketing materials recyclable (PET's, HDPE, PP and EDP) at Belém city. It was also observed the main social and structural problems faced by three of main cooperatives operating at Belém. Methodologically, a qualitative approach was used, through in loco interviews in the headquarters of the cooperatives. Besides, it wasobtained data from developed activities, working conditions observation and the obtaining of monthly production reports. From this research, it was observed that the cooperatives have several problems, both in the structure of the work environment and in the lack of awareness and environmental education of the population, which directly affect the monthly production of workers. As a result, an average of 28 tons of plastic waste are collected adding up the production of the three cooperatives studied and these sell the material collected to the company RIOPEL.